(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: There are high risks and potential hazards in the process of making Zwavelzuur Kalium (ZK) fertilizer. The risk varies according to the chemical used in the process. Identification of potential hazards and risks is required periodically to control the risks Objectives: To identify the potential hazards and risks in the process of making ZK fertilizer and to control the risk Methodology: This study is an observational study to observe the process of making ZK fertilizer and to conduct occupational health and safety risk management Results: There are various hazards can occur in ZK production including chemical hazards such as hazardous, toxic, reactive, irritant, and corrosive as well as physical or mechanical hazards which include altitude, machinery, equipment, noise, and temperature Conclusion: The highest risk assessment results on ZK production are in the reactor unit, which causes the risk of explosion. Risk control refers to the principle of the control hierarchy